Experimental study on normal deformation characteristics of filled rock joints with typical fluctuation morphology - Luo, Zhanyou; Zheng, Wei; Du, Shigui; Huang, Man; Wang, Changshuo (Frontiers in Earth Science, 2023)
The uneven deformation of filled rock joints subjected to ground stress can easily cause instability in engineering rock masses. Fluctuations in morphology and filling are the main factors affecting the normal deformation of filled rock joints. To study the effect of the degree of filling and the degree of morphology fluctuation on the normal deformation of filled rock joints, we conducted a systematic experimental study. First, rock joints with joint roughness coefficients of 1,5, 9, 13, and 17 were selected based on Barton’s typical curves. Then, filled rock joint samples were made using a self-developed filled rock joint sample mold and three-dimensional engraving technology. Lastly, compression tests were carried out to analyze the effect of the degree of filling and the degree of morphology fluctuation on the normal deformation characteristics of filled rock joints. The results show that the degree of filling significantly affects the normal deformation of filled rock joint samples. The normal deformation of filled rock joints has a nonlinear relationship with normal stress. The power function equation can well represent the normal closure deformation behavior of filled rock joints. Additionally, a relationship between the maximum closure deformation of filled rock joints and the degree of filling was established based on Bandis’s empirical formula. The proposed equation takes into account the effect of the degree of filling by replacing the rock joint opening with filling thickness, and the predicted values are in good agreement with the experimental results.